Unveiling the Role of Grammar Mastery: How Sentence Structure, Verb Usage, And Subject-Verb Agreement Shape Tenses Proficiency in English Learning - Yusuf, Faidah; Ali, Ameer (PANYONARA: Journal of English Education, 2025)
: This study looks at how well elementary school children can use language. It focuses on four main areas are basic sentence structure, proper verb use, subject-verb agreement, and the use of tenses. Since grammar is such an important part of teaching English, especially to elementary school teachers, the study's goals are to find out how well students are doing and how these skills relate to each other. A descriptive correlational method was used with a quantitative technique, and 117 bilingual students took part. A questionnaire was used to collect data, and Structural Equation Modeling-Partial Least Squares (SEM-PLS) was used to examine it. The results show that the subjects had different levels of competence, and there were significant correlations between the four parts of grammar. Basic Sentence Structure became an important factor that affected the correct use of verbs and subject-verb agreement, which in turn affected the use of tenses. The study shows how important it is for teacher education programs to teach grammar well and stress the value of combining subject knowledge with effective teaching methods to prepare bilingual teachers for their jobs. These data show how important it is to include focused interventions in teacher training programs to make sure that future elementary school teachers have the language and teaching skills they need to teach English well.